2015
DOI: 10.1620/tjem.237.287
|View full text |Cite
|
Sign up to set email alerts
|

Anemia Is a Risk Factor for Acute Kidney Injury and Long-Term Mortality in Critically Ill Patients

Abstract: Acute kidney injury (AKI) is a major health concern, because AKI is related with an increase in morbidity and mortality. Anemia is related to AKI in several clinical settings. However, the relationship between anemia and AKI and the effect of anemia on long-term mortality are unresolved in critically ill patients. A total of 2,145 patients admitted to the intensive care unit were retrospectively analyzed. We calculated a threshold value of hemoglobin associated with an increased risk of AKI and used this value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 23 publications
(23 reference statements)
2
44
0
8
Order By: Relevance
“…24 Anemia is a known risk factor for AKI, failed renal recovery, CKD progression, and renal-related mortality. [25][26][27][28] Decreased partial pressure of oxygen in the kidneys and oxidative stress contribute to acute tubular injury, glomerulosclerosis, and chronic tubulointerstitial damage. 28,29 Interstitial injury negatively impacts erythropoietin production, suppressing RBC production, a process perhaps underlying the low RBC counts we also observed.…”
Section: Rate Of Progression To Ckdmentioning
confidence: 99%
“…24 Anemia is a known risk factor for AKI, failed renal recovery, CKD progression, and renal-related mortality. [25][26][27][28] Decreased partial pressure of oxygen in the kidneys and oxidative stress contribute to acute tubular injury, glomerulosclerosis, and chronic tubulointerstitial damage. 28,29 Interstitial injury negatively impacts erythropoietin production, suppressing RBC production, a process perhaps underlying the low RBC counts we also observed.…”
Section: Rate Of Progression To Ckdmentioning
confidence: 99%
“…One respective study in Korea also reports that anemia was more prevalent in HM patients than those with solid tumors (79.4% vs. 50.4%), and HM patients also shares a higher risk of AKI and long-term mortality [29].…”
Section: Discussionmentioning
confidence: 95%
“…These pathologic changes may contribute to the heightened susceptibility of AKI and partial even non-recovery in patients with CKD. Anemia was also a common feature in HM patients, which could be caused by reduced hematopoietic capacity of bone marrow, hemodilution, frequent blood sampling, dysfunctional iron metabolism, nutritional deficiencies, diminished red blood cell survival, and a blunted cellular response to erythropoietin et al One respective study in Korea also reported that anemia was more prevalent in HM patients than those with solid tumors (79.4% vs. 50.4%), and HM patients also shared a higher risk of AKI and long-term mortality [26].…”
Section: Discussionmentioning
confidence: 99%